Faktor-Faktor Yang Mempengaruhi Kepuasan Mahasiswa Matematika Fmipa Unp Saat Belanja Online Dengan Menggunakan Analisis Faktor - Yunita, Hazarin Morela; Rizal, Yusmet (UNIVERSITAS NEGERI PADANG, 2023)
Customer satisfaction is the result of a comparison between expectations and reality that customers receive after consuming goods or services. One of the factors that influence online purchase satisfaction behavior based on satisfaction factors are product quality factors, price factors, service quality factors, emotional factors, and convenience factors. The purpose of this study is to find out about the factor analysis model and what factors influence the satisfaction of UNP Mathematics students when shopping online. The data used is primary data obtained from giving questionnaires to UNP Mathematics Student respondents and factor analysis is used to analyze the data. From the results of the study it was concluded that the factors formed were the first factor containing the variables of product quality, service quality, and emotional factors. The second factor contains price and convenience variables.